1982
DOI: 10.1038/jcbfm.1982.36
|View full text |Cite
|
Sign up to set email alerts
|

Does Endogenous Norepinephrine Regulate Potassium Homeostasis and Metabolism in Rat Cerebral Cortex?

Abstract: Summary:The role of endogenous cerebral norepinephrine (NE) as a mod ulator of transmembrane cation transport and energy metabolism was evalu ated by monitoring extracellular potassium ion activity ([K+jo) in vivo and by measuring cortical Na+,K+-ATPase activity and oxygen consumption in vitro, Ipsilateral cortical NE was depleted by unilateral 6-hydroxydopamine (6-OHDA) lesions of the locus ceruleus (LC), The contralateral cortex was used for control measurements, NE depletion had no effect on resting levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Despite this marked depletion of norepinephrine, neither the maximal capacity nor the affinity of specific ouabain binding to crude membranes of the cerebral cortex was significantly altered by the lesion (Table 1). These findings are consistent with previous results from this laboratory, which showed that LC lesion, and the resultant norepinephrine depletion of the cerebral cortex, was not associated with a significant decrease in Na+/K+-ATPase activity of cortical membrane preparations when assayed in vitro (19). More important, norepinephrine depletion had no effect on extracellular K+ concentrations in the rat cerebral cortex at rest, nor did it affect the kinetics of (20,21), who observed only a modest decrease (about 15%) in Na+/K+-ATPase activity and specific ouabain binding after cerebral norepinephrine depletion.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Despite this marked depletion of norepinephrine, neither the maximal capacity nor the affinity of specific ouabain binding to crude membranes of the cerebral cortex was significantly altered by the lesion (Table 1). These findings are consistent with previous results from this laboratory, which showed that LC lesion, and the resultant norepinephrine depletion of the cerebral cortex, was not associated with a significant decrease in Na+/K+-ATPase activity of cortical membrane preparations when assayed in vitro (19). More important, norepinephrine depletion had no effect on extracellular K+ concentrations in the rat cerebral cortex at rest, nor did it affect the kinetics of (20,21), who observed only a modest decrease (about 15%) in Na+/K+-ATPase activity and specific ouabain binding after cerebral norepinephrine depletion.…”
Section: Resultssupporting
confidence: 83%
“…The reaction mixture (0.25 ml) contained 2 mM TrisATP (vanadium-free grade), 100 mM NaCl, 2 mM MgCl2, 10 mM Tris buffer (pH 7.4), and [3H]ouabain (19)(20)(21) Ci/mmol, New England Nuclear; 1 Ci = 37 GBq) in concentrations that ranged from 5 to 500 nM. The amount of tissue protein ranged from 20 to 50 ,g for cortical membranes and from 50 to 100 ,g for cerebral microvessels.…”
Section: Methodsmentioning
confidence: 99%
“…Participation of adrenergic stimulation in cellular K + uptake, specifically at small but not at larger increases in [K + ] o after stimulation in vivo, was also suggested by Sick et al (). These authors studied kinetics of the return of [K + ] o to control levels in anesthetized rats with unilateral destruction of locus coeruleus, the origin of noradrenergic fibers to the brain, at different stimulated values of [K + ] o (resulting from different stimulation intensity).…”
Section: The Astrocytic Na+k+‐atpase Is Also Stimulated By Isoprotersupporting
confidence: 54%
“…That the clearance of extracellular potassium, elevated by cortical stimulation, is slowed by barbitu rate administration supports the former ex planation as the cause of slow cytochrome a.aj re-reduction with that drug [20]. On the other hand, cerebral NE depletion in Wistar rats does not alter the rate of extracellular potassium clearance after electrocortical stimulation [40,41], There is now evidence that the availability of substrates to re-reduce cytochrome a.aj after increased cortical ac tivity may be decreased when cortical NE is depleted because of decreased glycogenolysis [11], There is also ample evidence in the lit erature to suggest decreased substrate mobili zation in the cerebral cortex of aged rats. This is based on decreased phosphofructokinase activity, the rate-limiting enzyme in glycoly sis [24], and decreased NAD isocitrate dehy drogenase activity [29,47], an important en zyme in the Krebs cycle.…”
Section: Discussionmentioning
confidence: 99%